Simulation of the Effects of Forest Management and Water Protection Practices on Nutrient Exports in a Forested Boreal Catchment - Nieminen, Mika; Räsänen, Aleksi; Miettinen, Janne; Sarkkola, Sakari; Stenberg, Leena; Pukkala, Timo (My University, 2025)
There is an urgent need to improve water quality management in forested catchments, particularly in forestry-drained peatland areas. We utilized nutrient export models and forestry simulations to forecast the impact of forest management and water protection practices on nitrogen and phosphorus exports from forests to waters in the Kiiminkijoki catchment area, central Finland. Our simulations indicated that the choice between forest management systems (even-aged forestry, extended rotation length, continuous cover forestry, no forestry) may have a larger impact on nutrient exports from mineral soil forests than from drained peatland forests. Of the water protection practices, sedimentation ponds, peak runoff control dams, and riparian buffer zones may have little effect on nutrient exports, but wetland buffers in drained peatland forests may reduce nutrient exports to a significantly lower level. Our simulations suggested that forestry operators should consider continuous cover forestry and wetland buffers when trying to improve water quality in forested catchments.
Keywords: continuous cover forestry; rotation forestry; nutrients; water quality; wetland buffer